Household food-waste composting using a small-scale composter - Vich,Daniele Vital (2017)
Abstract Household food-waste composting is an attractive alternative for Brazilian waste management; however, there are few programs or studies regarding the implementation or management of this small-scale process. This study investigates the performance of food-waste composting using a simple and small-scale domestic composter. Three composting trials were conducted using food waste and wood chips in 10 L plastic bins using different filling schemes. In the first trial, the composter was filled weekly over two months. In the second, the composter was filled once with a mixture of food waste and 100% of the used wood chips from the previous trial. In the last third trial, the composter was filled with food waste and wood chips (50% of wood chips used in the second trial and 50% of untreated wood chips). The physical chemical parameters of the compost were monitored and the total coliforms and E. coli were measured. In all trials, the temperature varied between 26.7°C and 46.2°C throughout the process. The reduction in wet mass was 58-69%, while the reduction in dry mass was 37-61%. The pH value, the contents of carbon and nitrogen and the C/N ratio were in accordance with the values recommended in norm 25 (July, 2009) adopted by Brazil's Agriculture Ministry. Only the compost from Trial 2, which had 1900 MPN g-1 total solids, did not meet the E. coli standards; this was likely due to the fact that when the temperatures did not reach the thermophilic phase, the relatively long time the waste remains in the composter allows these pathogenic microorganisms to decay naturally.